Project Based Learning Model Assisted by Mind Mapping Media: Student Creativity in IPAS Lessons at Public Islamic Elementary - Wansyah, Rio; Fiteriani, Ida; Erfayliana, Yudesta (ETDC: Indonesian Journal of Research and Educational Review, 2025)
This study seeks to evaluate the impact of the Project Based Learning (PjBL) model, facilitated by mind mapping media, on enhancing students' creativity in science education. This research employs a quasi-experimental approach utilizing a nonequivalent control group design. This research was carried out in fourth grade at State Elementary Madrasah 2 in Bandar Lampung. Data acquisition via assessments, interviews, and observations. The analysis of data involves quantitative assessment utilizing the independent samples t-test. The study's results demonstrate a substantial and favorable impact of the Project Based Learning (PjBL) model, facilitated by mind mapping media, on students' creativity in science subjects. The findings stem from the independent sample t-test, revealing a significance value of 0.000, which is less than the significance threshold of 0.05. Moreover, the creativity of students engaged in the mind mapping-assisted project-based learning model was quantitatively superior to that of students involved in conventional learning. The substantial disparity in the average posttest scores between the experimental group (mean = 16.82) and the control group (mean = 12.18) is apparent. The efficacy of the Mind Mapping-assisted PjBL model in fostering creativity derives from the synergy between the student-centered learning paradigm and the application of visual cognitive tools. Project-based learning fosters a genuine and demanding educational atmosphere, motivating students to engage in exploration, collaboration, and problem-solving. Mind mapping is an effective tool for promoting non-linear thinking, visually organizing complex ideas, and integrating the brain's logical and creative functions.